Effectiveness of transcutaneous electrical diaphragmatic stimulation on respiratory muscle strength, lung volumes and capacities: a systematic review - Ferreira, Lucas Lima; Mello, Juliana R. C.; Brito, Marcus Vinicius C.; Cavenaghi, Odete Maud (Medicina (Ribeirao Preto), 2015)
Introduction: Transcutaneous electrical diaphragmatic stimulation (TEDS) is to stimulate the diaphragm, through rhythmic electrical stimulation short promoting a negative pleural pressure that can influence both the ventilation and in venous return and cardiac output, representing another important tool for respiratory therapy. Objective: To analyze the outcomes of the application of TEDS on respiratory muscle strength and lung volumes and capacities. Methods: Through a systematic review of the literature, clinical trials published between 2003 and 2013 were analyzed The search involved the LILACS, SciELO, MEDLINE and PEDro database, using the keywords diaphragm, respiratory muscles and physical therapy crossed with the descriptor electrical stimulation. Results: Six studies totaling 105 subjects, aged between 20 and 75 years and showed that the use of TEDS caused a significant increase (p <0,05) in maximal inspiratory pressure (MIP) and maximal expiratory pressure were included maximum (MEP), tidal volume (VT) and the volumes of inspiratory and expiratory reserve. Conclusion: The TEDS promotes an increase in respiratory muscle strength and in some lung volumes in healthy subjects and / or patients with chronic diseases or post-operative recovery.